2017
DOI: 10.1136/annrheumdis-2017-212285
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric lupus or not? Cerebral hypoperfusion by perfusion-weighted MRI in normal-appearing white matter in primary neuropsychiatric lupus erythematosus

Abstract: Primary NPSLE is characterised by significant hypoperfusion in cerebral white matter that appears normal on cMRI. The combination of DSC-MRI-measured blood flow in the brain semioval centre with conventional MRI may improve NPSLE diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 46 publications
6
37
1
Order By: Relevance
“…At first, the total WM was segmented using the Robust Statistics Segmenter tool and then the total WM volume was computed using the Model Maker tool. Lesion burden of small (<1 cm) WMH on T 2 /FLAIR sequences was classified according to their absolute number: grade 0 (no WMHs), grade 1 (mild: 1–5 WMHs), grade 2 (moderate: 6–10 WMHs), or grade 3 (severe: >10 WMHs) …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At first, the total WM was segmented using the Robust Statistics Segmenter tool and then the total WM volume was computed using the Model Maker tool. Lesion burden of small (<1 cm) WMH on T 2 /FLAIR sequences was classified according to their absolute number: grade 0 (no WMHs), grade 1 (mild: 1–5 WMHs), grade 2 (moderate: 6–10 WMHs), or grade 3 (severe: >10 WMHs) …”
Section: Methodsmentioning
confidence: 99%
“…Lesion burden of small (<1 cm) WMH on T 2 /FLAIR sequences was classified according to their absolute number: grade 0 (no WMHs), grade 1 (mild: 1-5 WMHs), grade 2 (moderate: 6-10 WMHs), or grade 3 (severe: >10 WMHs). 28…”
Section: Mr Image Acquisitionmentioning
confidence: 99%
“…The cerebral hypoperfusion of frontal, temporal, and partial areas has been observed in NPSLE patients by positron emission tomography (PET) and single‐photon emission computed tomography (SPECT) studies, which could provide early biomarkers for SLE (Kodama et al, ; Sahebari, Rezaieyazdi, Khodashahi, Abbasi, & Ayatollahi, ). Recently, MR perfusion imaging studies with dynamic susceptibility contrast (DSC) reported that the cerebral blood volume (CBV), and cerebral blood flow (CBF) of certain specific brain regions (e.g., posterior cingulate gyrus) were highly related to NPSLE (Gasparovic et al, ; Papadaki et al, ; Wang et al, ; Zimny et al, ). Compared to normal controls (NC), both hyperperfusion and hypoperfusion, were illustrated within gray (GM) and white matter (WM) in SLE patients (Gasparovic et al, ; Papadaki et al, ; Wang et al, ; Zimny et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, MR perfusion imaging studies with dynamic susceptibility contrast (DSC) reported that the cerebral blood volume (CBV), and cerebral blood flow (CBF) of certain specific brain regions (e.g., posterior cingulate gyrus) were highly related to NPSLE (Gasparovic et al, ; Papadaki et al, ; Wang et al, ; Zimny et al, ). Compared to normal controls (NC), both hyperperfusion and hypoperfusion, were illustrated within gray (GM) and white matter (WM) in SLE patients (Gasparovic et al, ; Papadaki et al, ; Wang et al, ; Zimny et al, ). Previous studies have demonstrated hypoperfusion within GM and WM in NPSLE compared to non‐NPSLE (Papadaki et al, ; Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation